Oligoasthenozoospermia with rare karyotype - Özbey, Ülkü; Yüce, Hüseyin (My University, 2007)
In a couple who had been investigated because of infertility, oligo-asthenozoospermia was diagnosed in man, by sperm analysis. Cytogenetic analyse, the karyotype of man was exhibited as 46, XY, t(9;15) (pter ?q21.1
Nadir karyotipli oligoastenozoospermi
Keywords: Chromosomal translocation; Male infertility; Meiotic pattern; Oligoasthenozoospermia